Life history traits of the gastropod-associated bacterivorous nematode Caenorhabditis brenneri (Nematoda: Rhabditida) - LOEL DALAN; VERONICA TAÑAN; MICHELLE ANNE DIANO; CESAR DEMAYO; MYLAH TABELIN; NANETTE HOPE SUMAYA (Society for Indonesian Biodiversity, 2024)
Abstract. Dalan L, Tañan V, Diano MA, Demayo C, Tabelin M, Sumaya NH. 2024. Life history traits of the gastropod-associated bacterivorous nematode Caenorhabditis brenneri (Nematoda: Rhabditida). Biodiversitas 25: 3106-3113. Caenorhabditis species are associated with decaying plant materials and invertebrates such as terrestrial gastropods. Few Caenorhabditis species have been studied regarding their ecology, genetics, development, and essential life history traits (LHT). In this study, we describe the life cycle of a free-living, wild-type, bacterivorous nematode, Caenorhabditis brenneri Sudhaus and Kiontke 2007, associated with the terrestrial slug Philippinella moellendorffi Collinge 1899 and account for the effects of food density and temperature on its population dynamics by employing the hanging drop technique. The bacterial food supply was sourced from the slug cadaver and identified as Alcaligenes faecalis (MT012081). C. brenneri was fed with varying bacterial densities (109 and 5×109 cells mL-1) and incubated at 20 and 25°C. The bacterial food density-temperature interaction was found to have no significant influence on the offspring production of C. brenneri. Moreover, the total fertility rate (TFR) and net reproductive rate (Ro) are higher in 109 cells mL-1 in both temperatures (TFR at 20°C: 139; 25°C: 169 and Ro at 20°C: 134; 25°C: 156). Whereas the alternative generation time (To, T1, T) and population doubling time (PDT) are faster at 25°C in both bacterial densities, the intrinsic rate of natural increase (rm) is faster at lower temperatures (20°C) in both bacterial densities. The average lifespan of C. brenneri is seven days when fed with A. faecalis. Offspring somatic growth (body length and width) was influenced by bacterial food density-temperature interaction with increased length and girth observed in higher bacterial density and temperature in our knowledge. This study is the first attempt to use A. faecalis, a wild-type bacterium from the terrestrial slug P. moellendorffi cadaver, as the bacterial food source for a Caenorhabditis LHT analysis.